ERGONOMIC ANALYSIS OF WORK IN CIVIL ENGINEERING OFFICES (Fiep Bulletin - online, 2016)
Progressively, the ergonomics is gaining ground in several productive and service sectors. Thus this article refers to an ergonomic analysis of work at two companies of project in the field of Civil Engineering, located in the city of Curitiba, in the state of Paraná, Brazil. The objectives were to compare the standard data with the reality in the offices and to verify the knowledge of the employees concerning ergonomics. To this end, measurements of noise, illuminance and furniture of the workplaces were performed in each company, the Nordic Musculoskeletal Questionnaire and a questionnaire about ergonomics and workplace exercises were applied as well. Through the analysis of all the results together, it was observed that the levels of noise and illuminance were not in accordance with the regulatory standard and also that there is the need of ergonomics improvement in both companies.
Keywords: Ergonomic Analysis of Work; Offices; Musculoskeletal System.